Beyond Brexit? : how to assess the UK's future - Morphet, Janice (Policy Press shorts. Insights., 2017)
Takes a long term view on the range of institutional and operational options available to the UK, EU and other international institutions seeking to influence Brexit negotiations and outcomes.